Home phototherapy for patients with vitiligo: challenges and solutions - Smith MP; Ly K; Thibodeaux Q; Bhutani T; Nakamura M (Dove Medical Press, 2019)
Mary Patricia Smith,1 Karen Ly,1 Quinn Thibodeaux,1 Tina Bhutani,1 Mio Nakamura21Department of Dermatology, University of California San Francisco, San Francisco, CA, USA; 2Department of Dermatology, University of Michigan, Ann Arbor, MI, USAAbstract: Vitiligo is a chronic autoimmune condition involving selective dysfunction and destruction of melanocytes in the skin, hair, or both. The typical presentation is well-demarcated depigmented skin patches. Given vitiligo is the most common cause of depigmentation worldwide and early disease responds best to treatment, prompt diagnosis and proactive management of vitiligo are critical. While a wide variety of treatments has demonstrated variable effectiveness in treating vitiligo, phototherapy remains standard of care because of its proven efficacy and favorable side effect profile. However, many patients with vitiligo are unable to access affordable, consistent, or convenient phototherapy. To address these issues, home-based phototherapy has emerged as a patient-centered alternative. The purpose of this review is to discuss management of vitiligo with a specific focus on access to home-based phototherapy (HBPT) for patients with this condition. Key challenges to HBPT include misperceptions around safety and efficacy, inadequate physician education and training, insurance and financial barriers, and appropriate patient selection. Solutions to these challenges are presented, such as approaches to improve physician education and increasing the evidence surrounding the effectiveness and safety of this treatment for vitiligo. In addition, various practical considerations are discussed to guide dermatologists on how to approach HBPT as a treatment option for patients with vitiligo.Keywords: vitiligo, pigmentation disorders, phototherapy, photomedicine